Merchant acceptance, costs, and perceptions of retail payments: A Canadian survey - Carlos Arango; Varya Taylor (Bank of Canada, 2008)
Using the results of a survey on accepted means of payment, the authors examine merchant preferences and perceptions of retail payment reliability, risk, and costs; the share of each type of payment method over total sales; and the costs involved in accepting payments. Models are developed for each means of payment in order to determine how merchant characteristics may influence their responses. The authors find that the average transaction value, total transaction volume, and/or number of point-of-sale terminals influence merchant perceptions. The authors confirm that merchant preferences are determined by their perceptions and that the intensity of payment use is also important. Furthermore, the authors find that, aside from the initial decision to accept a payment method, merchants have little influence over the payment decisions made by consumers. These last two findings are indicative of the two-sided nature of payments. The marginal costs of accepting payment methods are also estimated and compared, and payment card processing fees are examined.
Keywords: E41; L2; 330; Bank notes; Einzelhandel; Verbraucher; Bank; Zahlungsverkehr; Bargeldloser Zahlungsverkehr; Geld; Kanada